1970
DOI: 10.1128/jvi.5.1.51-59.1970
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 and Type 2 Herpes Simplex Viruses: Serological and Biological Differences

Abstract: Forty isolates of herpes simplex virus were compared by means of cross-neutralization curves. The 11 oral isolates were serotype 1, and all 29 genital/anal isolates were serotype 2. The cytopathic effects of the two serotypes were consistently different. Passage of strains of type 1 and type 2 in mice and in rabbits yielded two variants, although the majority of the strains remained unchanged serologically and in their cytopathic effects. The two variants were derived from type 1 strains and differed from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
2

Year Published

1971
1971
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 9 publications
3
25
2
Order By: Relevance
“…Whether this antigenic difference is of sufficient magnitude and stability to warrant "type" distinctions is a matter of present controversy (6,9). Although antigenic character does not appear to vary with EOP in this or another study (8), or with other markers (12,13), there is great diversity in the degree of relatedness between strains within groups. Hampar et al (6) have suggested that H. hominis strains should be classified into one serological group as a species by the use of 7S antibodies and that late 19S antibodies should be used for determining subtypes within that species.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Whether this antigenic difference is of sufficient magnitude and stability to warrant "type" distinctions is a matter of present controversy (6,9). Although antigenic character does not appear to vary with EOP in this or another study (8), or with other markers (12,13), there is great diversity in the degree of relatedness between strains within groups. Hampar et al (6) have suggested that H. hominis strains should be classified into one serological group as a species by the use of 7S antibodies and that late 19S antibodies should be used for determining subtypes within that species.…”
Section: Discussioncontrasting
confidence: 51%
“…The examination of these herpesvirus strains suggests, as have the results of other studies (2,9,12), that neutralization divides strains into two rather distinct groups, which also differ in biological characteristics. Whether this antigenic difference is of sufficient magnitude and stability to warrant "type" distinctions is a matter of present controversy (6,9).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Two distinct variants of HSV exist. HSV‐1 is usually located in the face, while HSV‐2 is responsible for genital infections 3 . If the identification of the virus is needed, the liquid in a fresh blister is subjected to PCR or negative staining can be performed using electron microscopy 4…”
Section: Examples For Rapid Detection Of Infectious Agentsmentioning
confidence: 99%
“…Viru8e8. Vienna Herpes simplex viruses form one serologic group, but minor antigenic differences have resulted in a classification into two types (Plummer, Waner, Phuangsab & Goodheart, 1970): type I is associated with non-genital and type II with genital infections.…”
mentioning
confidence: 99%